1997
DOI: 10.1099/00222615-46-1-80
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactulose on short-chain fatty acids and lactate production and on the growth of faecal flora, with special reference to Clostridium difficile

Abstract: Lactulose exerts a beneficial effect on hepatic encephalopathy by decreasing toxic shortchain (iC4-nC6) fatty acid (isobutyrate, butyrate, isovalerate, valerate, isocaproate and caproate) production. However, the precise mechanism by which lactulose exerts this effect remains uncertain. This study investigated the effect of lactulose on faecal flora, particularly CZostridium difBciZe, which produces mostly iC4-nC6 fatty acids. An in-vitro faecal incubation system was used to estimate how lactulose influences p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 25 publications
(10 reference statements)
4
29
0
Order By: Relevance
“…Alternatively, the reduction in isobutyrate may be due to modulation of the gut microbial ecology. Ito et al (61) have shown that lactulose supplementation reduces the fecal concentrations of SCFAs (isobutyrate, butyrate, isovalerate, valerate, isocaproate, and caproate), which may be related to suppression of fecal micro-organisms producing these SCFAs, especially C. difficile.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, the reduction in isobutyrate may be due to modulation of the gut microbial ecology. Ito et al (61) have shown that lactulose supplementation reduces the fecal concentrations of SCFAs (isobutyrate, butyrate, isovalerate, valerate, isocaproate, and caproate), which may be related to suppression of fecal micro-organisms producing these SCFAs, especially C. difficile.…”
Section: Discussionmentioning
confidence: 98%
“…Another interesting finding was the diet effect on gastric, ileal, and colonic caproate, which differed among gut sites, indicating that different caproate-producing bacteria dominated at the three gut sites. Caproate-producing bacteria can be found within different Clostridium clusters, such as clusters I, IV, XI, and XIV (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…An inhibitory effect of lactulose on growth of C. difficile in human fecal cultures has also been reported (20). Lactobacilli predominated in these cultures, while bacteroides, bifidobacteria, and enterobacteria were suppressed.…”
mentioning
confidence: 92%